Vocational interest, skills, and counselling as correlates of unemployed graduates’ readiness to enter low-paying occupations in Delta State of Nigeria - Tibi, P. I. (International research journal of management, IT and social sciences, 2023)
There is a high level of unemployment amongst National Youth Service Corps-discharged graduates of universities and polytechnics in Nigeria, especially in Delta State. This necessitated guiding these graduates to take to low-skill, low-paying jobs, as an alternative to redundancy and the attendant indulgence in anti-social behavior. The purpose of this study was to investigate the relationship between vocational interest, skills possessed and vocational guidance techniques, and unemployed graduates’ readiness to enter into low-skill occupations. A research hypothesis was formulated for the correlational design study. Three instruments: the Modified Bakare Vocational Interest inventory (MB VII), the vocational skills possessed inventory (VSPI), and the vocational guidance techniques (counseling) were used. The study population comprised of all unemployed NYSC-discharged graduates in Delta State. Purposive sampling was used to select two Local Government Areas (LGA’s) from each of the three Senatorial Districts of Delta State (Six LGA’s). Random sampling was used to obtain two hundred and forty respondents from the six LGAs. Data were analyzed using multiple regression analysis. Results indicated that vocational interest, skills possessed and counseling had significant relationships with unemployed graduate's readiness to enter low-skill occupations. They were all predictors of entry into low-skill jobs except counseling.